Entwicklung einer sprachenpolitischen Maßnahme in einem multinationalen Unternehmen in der Tschechischen Republik - Lucie Černá (Acta Universitatis Carolinae: Philologica, 2025)
The article presents partial results of a study on market-oriented multilingualism and its strategic management in the workplace of a multinational company in the Czech Republic. The study incorporates the language management theory and the ethnography of communication. The data were primarily based on participant observations and a complete integration into the field of study. The presented example illustrates how language policy measures are being created, by whom, under what circumstances, and which methods influence the decision-making process.